LKPD berbasis Model Problem Based Learning Berorientasi pada Kemampuan Numerasi: Bagaimana Respon Siswa? - Salsabila, Nilza Humaira; Sripatmi, Sripatmi; Tyaningsih, Ratna Yulis; Novitasari, Dwi; Triutami, Tabita Wahyu (Media Pendidikan Matematika, 2024)
This research aims to produce mathematics learning media in the form of Student Worksheets (LKPD) based on the Problem Based Learning (PBL) Model in statistical material oriented towards numeracy skills. The development of worksheets was carried out based on the development model by Plomp. One of the qualities of the media developed includes practical aspects. The practicality of the worksheets learning media was assessed by students by filling out a response questionnaire on the use of worksheets. The developed worksheets meets practical criteria if the average score of students' responses to mathematics learning media is in the minimum good classification (X>28). The response questionnaire for using worksheets was filled in by students in grades 8.4 and 8.5 of MTsN 1 Mataram, totaling 51 students. The research results show that the worksheets meets practical criteria. Based on the results of student responses, students' use of worksheets shows an average score of 32.48 which has a good classification. Thus, the worksheets developed is easy and useful to use in mathematics learning.